Flow field dynamics of large-scale experimentally produced downburst flows. Issue 188 (May 2019) - Junayed, Chowdhury; Jubayer, Chowdhury; Parvu, Dan; Romanic, Djordje; Hangan, Horia
Abstract: This study characterizes the mean and turbulent flow fields resulting from several large-scale downbursts simulated in the Wind Engineering, Energy and Environment (WindEEE) Dome at Western University. Detailed three-component velocity Cobra probe measurements are conducted for several Reynolds numbers and downburst height to diameter ratios. The wind speed records at a comprehensive number of heights and radial distances are analyzed using a moving average approach similarly employed in some full-scale campaigns. A reasonable averaging time is determined and the analysis of the turbulent flow is carried out using first and second order statistics and the similarities with full-scale data is presented. Moreover, Particle Image Velocimetry (PIV) measurements are carried out in order to investigate the dynamics of downburst vortices for the same Reynolds numbers and the same downburst height to diameter ratios as in the Cobra probe measurements. The structure and evolution of the primary downburst vortex from PIV are compared with existing full-scale data. Highlights: Characterizes mean and turbulent flow fields for large scale experimentally simulated downbursts. Analyzes simulated downburst wind speed time histories similar to the approaches used for full scale downburst records. Investigates turbulence characteristics relevant to wind loading of structures. Primary vortex structure and its evolution for the simulated downbursts are compared with the available full scale records.